Endoscopic resection of the submandibular gland: a new surgical approach - Sumeet Karn (Society of Surgeons of Nepal, 2016)
Introduction: Submandibular gland excision is traditionally performed by the transcervical approach. To avoid or reduce visible scarring and nerve injury, diverse innovative surgical trials have been reported. Here we report a patient who had an endoscopic submandibular gland resection via a hairline incision.